(untitled) (Revista de História da UEG (REVHIST), 2025)
The text addresses the relationship between history and city, drawing on the poetic work of Torquato Neto and some of his contemporaries to study the city of Teresina, capital of the Brazilian state of Piauí. In light of Michel de Certeau’s conceptual references, it is proposed that the “Spectre Torquato Neto” reconfigured the city of Teresina, blurring its postcards and shattering it into multiple invisible cities. The text proposes that the act of walking through the city implies both speaking and making a reading of the city. The main argument of the text consists of demonstrating that cities, outside of utopian-urbanist discourse, only exist in their invisible form, carried and constantly recomposed in the hidden and deep region, the desiring machinery, which we call subjectivity. Keywords: History of Brazil; City; Torquato Neto.